Inward Outward Signaling in Ovarian Cancer: Morpho-Phospho-Proteomic Profiling Upon Application of Hypoxia and Shear Stress Characterizes the Adaptive Plasticity of OVCAR-3 and SKOV-3 Cells - Bileck, Andrea; Bortel, Patricia; Kriz, Michelle; Janker, Lukas; Kiss, Endre; Gerner, Christopher; Del Favero, Giorgia (Frontiers in Oncology, 2022)
With the onset of resistance, ovarian cancer cells display almost unpredictable adaptive potential. This may derive from the tumor genetic ancestry and can be additionally tailored by post translational protein modifications (PTMs). In this study, we took advantage of high-end (phospho)-proteome analysis combined with multiparametric morphometric profiling in high-grade serous (OVCAR-3) and non-serous (SKOV-3) ovarian carcinoma cells. For functional experiments, we applied two different protocols, representing typical conditions of the abdominal cavity and of the growing tumor tissue: on the one side hypoxia (oxygen 1%) which develops within the tumor mass or is experienced during migration/extravasation in non-vascularized areas. On the other hand, fluid shear stress (250 rpm, 2.8 dyn/cm2) which affects tumor surface in the peritoneum or metastases in the bloodstream. After 3 hours incubation, treatment groups were clearly distinguishable by PCA analysis. Whereas basal proteome profiles of OVCAR-3 and SKOV-3 cells appeared almost unchanged, phosphoproteome analysis revealed multiple regulatory events. These affected primarily cellular structure and proliferative potential and consolidated in the proteome signature after 24h treatment. Upon oxygen reduction, metabolism switched toward glycolysis (e.g. with upregulation hexokinase-2; HK2) and cell size increased in concerted regulation of pathways related to Rho-GTPases and/or cytoskeletal elements, resembling a vasculogenic mimicry response. Shear stress regulated proteins governing cell cycle and structure, as well as the lipid metabolism machinery including delta(14)-sterol reductase, kinesin-like proteins (KIF-22/20A) and actin-related protein 2/3 complex. Independent microscopy-based validation experiments confirmed cell-type specific morphometric responses. In conclusion, we established a robust workflow enabling the description of the adaptive potential of ovarian cancer cells to physical and chemical stressors typical for the abdominal cavity and supporting the identification of novel molecular mechanisms sustaining tumor plasticity and pharmacologic resistance.